Information Systems Strategic Planning in Improving Organizational Operational Management with Ward and Peppard - Fachrully, Fachrully Adira Muhammad; Suryana, Nana (CV. Generasi Intelektual Digital, 2024)
The Sarijadi Village Karang Taruna is one of the social institutions in the Sarijadi Village area which plays a role in improving social welfare for the community, of course by holding activities such as social services. To support these activities, Karang Taruna needs more contributions from its own community, both in the form of suggestions and criticism, as well as relevant data. Not only does that data exist, but data such as attendance lists, schedule boards, minutes, and so on are needed for future needs. In collecting this data, Karang Taruna must have good and structured operational management so that the data it already has can be stored properly and minimize data loss. In improving operational management, Karang Taruna can use an information system, so that the resources they have can be used efficiently and effectively. In developing an organization's operational management information system, a good and structured information system strategic planning is required. In writing this article, the researcher used the Ward and Peppard research method. Where by using this method, information system strategic planning, Karang Taruna can better understand its external environment, help adapt, and improve operational management. Several strategic planning techniques such as Value Chain Analysis, Five Forces Analysis, and SWOT Analysis are used to analyze the internal and external environment. In the end, this research can produce recommendations for organizations in establishing an IS/IT unit and improving operational management for organizational sustainability.